2017
DOI: 10.1016/j.jaci.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

IgE sensitization in relation to preschool eczema and filaggrin mutation

Abstract: PSE is associated with IgE sensitization to both food allergens and aeroallergens up to 16 years of age. FLG mutation is associated with IgE sensitization to peanut but not to other allergens. Sensitized children with preceding PSE are more often polysensitized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…Previous studies have found that children that carry a FLG mutation have an increased risk of peanut allergy even after adjusting for eczema . In this study, eczema seemed to be the overriding factor for peanut sensitization; however, it should be noted that FLG mutations were quite low in BAMSE (7.14%) in comparison with other population‐based cohorts . Tree nut and/or soya allergy by age 8 was also associated with primary peanut sensitization at age 8 years; co‐existent peanut and tree nut allergy have been shown in numerous studies, whereas co‐existent soya and peanut allergy are reportedly low in other populations …”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies have found that children that carry a FLG mutation have an increased risk of peanut allergy even after adjusting for eczema . In this study, eczema seemed to be the overriding factor for peanut sensitization; however, it should be noted that FLG mutations were quite low in BAMSE (7.14%) in comparison with other population‐based cohorts . Tree nut and/or soya allergy by age 8 was also associated with primary peanut sensitization at age 8 years; co‐existent peanut and tree nut allergy have been shown in numerous studies, whereas co‐existent soya and peanut allergy are reportedly low in other populations …”
Section: Discussioncontrasting
confidence: 57%
“…The phenotype, genotype, and mouse models have all recently been reviewed [185, 187-190]. In addition, filaggrin ( FLG ) deficiency can lead to impaired keratinization and defective skin barriers, which result in ichthyosis vulgaris and in some patients with elevated serum IgE [191-193]. It is usually categorized as an inherited disorder of keratinization.…”
Section: Other Syndromes In Which Ige Levels Are Highmentioning
confidence: 99%
“…Moreover, food allergy, oral allergy syndrome, and eosinophilic esophagitis are commonly associated with AD [116]. There is evidence that the skin might be the starting point of the atopic march, i.e., (1) mutations in filaggrin, a key barrier protein, have been reported to be associated with severe eczema and bronchial asthma as well as food allergy [117, 118], and (2) epicutaneous sensitization to proteins (food and pollen) paves the way for developing food allergy and airway allergic diseases [119-121]. …”
Section: Pathogenenic Mechanismsmentioning
confidence: 99%